Math11U

posted by .

Simplify each trigonometric expression

a) Sin(theta)Cot(theta)-Sin(theta)Cos(theta)

c)(sin x + cos x)(sin x - cos x)+ 2 cos(squared)x

  • Math11U -

    sinØcotØ - sinØcosØ
    = sinØcosØ/sinØ - sinØcosØ
    = cosØ - sinØcosØ
    = cosØ(1-sinØ)

    (sin x + cos x)(sin x - cos x)+ 2 cos(squared)x
    = sin^2 x - cos^2 x + 2cos^2 x
    = sin^2x + cos^2x
    = 1

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra

    Can someone please help me do this problem?
  2. Trig

    Which expression equivalent to: cos(theta + pi/2). A)cos theta B)-cos theta C)sin theta D)-sin theta my book doesnt give examples of this but my crack at it would be C b/c distributive property?
  3. Algebra II

    Which of the following expressions are not equal to 1?
  4. Calculus

    I wanted to confirm that I solved these problems correctly (we had to convert the polar curves to Cartesian equations). 1.rcos(theta)=1 x=1 2.r=2*sin(theta)+2*cos(theta) r^2=2rsin(theta)+2rcos(theta) x^2+y^2=2y+2x (a little unsure …
  5. Algebra II

    Multiple Choice Which expression is NOT equivalent to 1?
  6. Precalculus check answers help!

    1.) Find an expression equivalent to sec theta sin theta cot theta csc theta. tan theta csc theta sec theta ~ sin theta 2.) Find an expression equivalent to cos theta/sin theta . tan theta cot theta ~ sec theta csc theta 3.) Simplify …
  7. Precalculus check answers help!

    1.) Find an expression equivalent to sec theta sin theta cot theta csc theta. tan theta csc theta sec theta ~ sin theta 2.) Find an expression equivalent to cos theta/sin theta . tan theta cot theta ~ sec theta csc theta 3.) Simplify …
  8. Precalculus with Trigonometry

    Prove or disprove the following Identities: cos(-x) - sin(-x) = cos(x) + sin (x) sin raised to the 4 (theta) - cos raised to the 4 (theta) = sin squared (theta) - cos squared (theta) cos (x+(pi)/(6)) + sin (x - (pi)/(3)) = 0 cos(x+y)cos(x-y) …
  9. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …
  10. Trigonometry

    Prove the following identities: 1. (tan theta - sin theta)^2 + (1-cos theta)^2 = (1-sec theta) ^2 2. (1-2cos^2 theta) / sin theta cos theta = tan theta - cot theta 3. (sin theta + cos theta ) ^2 + (sin theta - cos theta ) ^2 = 2 Thank …

More Similar Questions